Scribal tools in ancient Israel a study of biblical Hebrew terms for writing materials and implements - Zhakevich, Philip 1983- (University Park Penn State University Press, 2020)
COVER Front -- Copyright Page -- Table of Contents -- Figures and Tables -- Acknowledgments -- Abbreviations -- Chapter 1: Introduction -- Chapter 2: Papyrus -- Chapter 3: Stone and Plaster -- Chapter 4: Skins, Scrolls, Tablets, Ostraca, and Uncommon Writing Surfaces -- Chapter 5: Scribal Instruments and Glyptics -- Chapter 6: Egypt's Influence on Canaan and Ancient Israel -- Chapter 7: Conclusion -- Works Cited -- Ancient Sources Index -- Subject Index.
Description based on publisher supplied metadata and other sources
Keywords: Writing; Electronic books